Jo MacDonald saw a pond - Quattlebaum, Mary (Dawn Publications, 2011)
In this version of the classic song "Old MacDonald Had a Farm," the farmer's granddaughter discovers the creatures living at a pond. End notes present facts, outdoor activities, and games related to this lively ecosystem.